Pemetaan Industri Kreatif Dan Penentuan Kompetensi Inti Bangkalan - Fitri Agustina; Nachnul Ansori; Tegar Pradana F.A (Jurnal Teknik Industri, 2013)
Determining core competence for creative industry which is characterized by utilizing creativity, skill and individual talent is the crucial selection process. It is because the output of creative industry as well as products and utilization of creativity are rapidly developed. This research discusses about mapping creative industry and determining core competence for creative industry in Bangkalan district based on the variable of gross domestic product, number of worker, international trade and number of firm. The method adopted for core competence determination is an integrated Analytical Hierarchy Process (AHP) and Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). The result of mapping creative industry shows that art, craft, design, video or film and publishing are included in it. Meanwhile craft subsector is determined as a core competence that is focused in Bangkalan district.